A Case Study on Eka Kushta (Psoriasis) (AYUSHDHARA, 2022)
In present generation beauty a combination quality of such as shape ,colour, an attractive and engaging personality, typically one who uses this impress others but that should be maintain by healthy habits. But due to Pradnyparadha and some of psychological cause or week daring, less immunity power one should suffer from many different skin diseases. Unhealthy food, sedimentary lifestyle and negative thinking cause Vikruta Twak vikarasa among them Ek kustha is one of the most guilty looking and irritating disease. The digestive fire Agni also get Manda consuming red met non-veg food and drinks are more prone to get skin diseases like psoriasis or many auto immune disorders. Our classics mentioned the skin disease in Kustha chapter in Charaka Samhita and as well as other Samhitas. For this many different Chikitsas like Shodana shaman, Rakta mokshana etc are explained in our classics.